Green synthesis of colloidal gold nanoparticles using latex from Hevea brasiliensis and evaluation of their in vitro cytotoxicity and genotoxicity - Santos, Natália M. [UNESP]; Gomes, Andressa S. [UNESP]; Cavalcante, Dalita G.S.M. [UNESP]; Santos, Luis F. [UNESP]; Teixeira, Silvio R. [UNESP]; Cabrera, Flávio C. [UNESP]; Job, Aldo Eloizo [UNESP] (Institution of Engineering and Technology (IET), 2019)
Latex extracted from Hevea brasiliensis tree has been used as a green alternative for preparing gold nanoparticles (Au NPs); however, no study evaluating the cytotoxic and genotoxic potential of Au NPs synthesised using H. brasiliensis has been published. The present study aimed to synthesise and characterise colloidal Au NPs using latex from H. brasiliensis and to evaluate their in vitro cytotoxicity and genotoxicity. Ideal conditions for the green synthesis of Au NPs were studied. In vitro cytotoxicity and genotoxicity of Au NPs in CHO-K1 cells was also evaluated. Our findings indicated that the ideal synthesis conditions of pH, temperature, reduction time, and concentrations of latex and HAuCl 4 were 7.0, 85°C, 120 min, 3.3 mg/mL, and 5.0 mmol/L, respectively. LC50 24 h of Au NPs was 119.164 ± 5.31 μg/mL. Lowest concentration of Au NPs tested presented minimal cytotoxicity and genotoxicity. However, high concentrations of Au NPs promoted DNA damage and cell death via apoptosis. On the basis of these findings, the authors optimised the use of an aqueous solution of H. brasiliensis latex as a reducing/stabilising agent for the green synthesis of Au NPs. Low concentrations of these NPs are biocompatible in normal cell types, suggesting that these NPs may be used in biological applications.